Company Law, Oppression of Minority S.181 Companies Act 1965: Re Kong Thai Sawmill (Miri) Sdn Bhd - Lim, M.H.K. (Journal of Malaysian and Comparative Law, 2018)
Company Law, Oppression of Minority S.181 Companies Act 1965: Re Kong Thai Sawmill (Miri) Sdn Bhd